Twenty Years of Military Prehospital Care in the Eastern Sovereign Base Area, Cyprus. Issue 1 (17th July 2019) - Halle-Smith, James Michael; Ahmad, T; Mason, G; Barlow, A; Gout, S
Abstract : Introduction: The Medical Reception Station (MRS) in Dhekelia provides a prehospital emergency care (PHEC) service for the Eastern Sovereign Base Area and surrounding Cypriot towns. This service has been evaluated previously but some important aspects of care have not yet been measured. The primary aim of this study was to undertake the most comprehensive service evaluation of the demand for the PHEC service at MRS Dhekelia over a 12-month period. The secondary aim of this study was to compare findings in 2018 to those in 1995–1998 and 2013–2016. Methods: All calls to the PHEC team between 01/07/2017 and 30/06/2018 were reviewed and compared with previously reported data from 1995 to 1998 and 2013 to 2016. Data were collected from the occurrence book, the logbook used by the PHEC team to record the details of each call. Results: There were 164 calls to the PHEC service during the current study period. The number of activations has decreased since the 2013–2016 period but remains greater than 1995–1998. In every month there was a call to a scene where more than one casualty was present, with the highest number being nine patients at one call. More calls were received during the day (55%). There were more calls because of trauma than medical complaints (55% vs 45%). Trauma calls have reduced over 20 years. The frequency of neurological and psychiatric complaints has increased over 20 years. Conclusions: The PHEC service at MRS Dhekelia is frequently used. The team consistently face with scenes with more than one casualty. Trauma is becoming less frequent but psychiatric and neurological complaints are increasingly common. These findings are important for training and service provision.